Women and development - Thomas, Jesy (2009)
Women's role in the productive sector has always been dictated by the economic advancements of the time. Their responsible position in the traditional society underwent a drastic change with the penetration of capital into the productive sectors. This paper seeks to analyse the process by which a major shift in the role of women occurred in the course of the economic advancements over the years. - Reproduced.
Keywords: Women and development